The Effect of State Solvency on Bank Values and Credit Supply: Evidence from State Pension Cut Legislation - Cohen, Lee Jeremy; Cornett, Marcia Millon; Mehran, Hamid; Tehranian, Hassan (Journal of Financial and Quantitative Analysis, 2018)
We find the financial condition of states impacts bank credit supply through their municipal bond holdings. In particular, we treat sudden political and statutory actions during the 2011 union bargaining rights debates in Wisconsin and Ohio as exogenous shocks to state solvency. We show bank valuations and municipal bond spreads adjust to the announcements, and, over longer horizons, a new lending channel linked to state solvency emerges, whereby banks supply credit as municipal bond appreciations free up capital.